The effects of vision training, neck musculature strength, and reaction time on concussions in an athletic population - Honda, Justin; Chang, Seung Ho; Kim, Kijeong (Journal of exercise rehabilitation, 2018)
A concussion is a major concern across the athletic population. Pre-vention of concussions can lead to a decrease of 3.8 million concus-sions that occur annually in the United States. Vision training, increas-ing neck musculature strength and quick reaction times are thought to be ways to prevent concussions. The purpose of this study is to review the literature on vision training, neck musculature, and reaction time, and how these interventions can prevent concussions. Upon review of the literature, vision training is proven to prevent concussions in a col-legiate football setting, but there is no literature on different levels or sports. There are inconclusive results on whether neck musculature strength prevents concussions. There are substantial results conclud-ing reaction time does prevent concussions by allowing the athlete to protect and anticipate head impact lessening the severity of the blow to the head. More research needs to be done for all three interventions to prove across all ages and levels of every sport that vision training, neck musculature strength, and reaction time prevent concussions in an ath-letic population. If proven true, practitioners in an athletic setting can use vision training, increasing neck musculature strength, and increas-ing reaction time as interventions to help prevent concussions in an athletic population.